Heavy ion storage and acceleration in the HESR with stochastic cooling and internal target. (26th November 2015) - Stockhorst, H; Katayama, T; Lehrach, A; Lorentz, B; Maier, R; Prasuhn, D; Stassen, R
Abstract: Heavy ion stochastic momentum cooling is investigated under the constraint of the present concept of the high energy storage ring (HESR). A bare uranium beam is injected from the collector ring into the HESR at 740 MeV u −1 and a beam preparation for an internal target experiment is outlined. Further the acceleration of the ion beam to 4.5 GeV u −1 is considered and an internal target experiment is studied. The simulations include the beam-target interaction involved with a hydrogen target. The capability of momentum filter cooling is envisaged and the possibility of time-of-flight momentum cooling is examined at lower energies where the revolution harmonics begin to overlap.